Metaphorical Thinking Approach as a Strategy for Solving Algebraic Problems in the Daily Life of Phase D Students in Mathematics Learning - Kursius, Catherine Mentaya; Istadi, Istadi; Muttaqien, Anwar (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
The Metaphorical Thinking approach in learning mathematics algebra material in the Independent Curriculum provides students with a more meaningful experience of the understanding process because they can see, form and map mathematical concepts to experiential concepts to practice solving everyday life problems in Algebraic form. This research is a library research study supported by interviews at SMP Negeri 3 Sampit. The research was carried out by collecting data from various sources regarding the difficulties of Phase D (SMP) students in algebra material and the metaphorical thinking approach to see the achievement of meaningful understanding of mathematics. With the characteristics of Metaphorical Thinking, students can carry out mathematical problem-solving activities, especially algebraic mathematical problems, so as to find meaningful understanding. Then carry out data analysis using descriptive analysis to determine the effect of the metaphorical thinking approach on the daily life problem solving abilities of phase D students in algebra material.